The Study of Airborne Germ Numbers in Delivery Room - Dewi Andika; Haryanto Haryanto (Lambung Mangkurat, 2022)
Hospital facilities, such as delivery rooms, can potentially cause nosocomial infections caused by germs, one of which is through the spread of germs in the air. Various factors, such as temperature, humidity, lighting, and occupancy density, can affect the presence of airborne germs. This study aimed to determine the quality of airborne germ numbers in the delivery room and the effect of occupancy density and physical environment on airborne germ numbers. The method used is the univariate analysis and Spearman’s Rank test. This type of research includes descriptive research with laboratory tests, using data from examining air germ numbers. The tools used are MAS 100 NT and ThermoHygrometer. The average result of the number of airborne germs was 202.08 CFU/m3. Temperature and humidity obtained an average of 23.53°C and 65.68%. The analysis results of occupancy density and airborne germs are p=0.742; rho = 0.071, room temperature and air germs, namely p = 0.806; rho=-0.053, room humidity and air germs, namely p=0.284; rho=-0.228. The factors in this study showed an insignificant relationship to airborne germs (p value> 0.05).